Are magnetic resonances practical transport controllers in fusion plasmas? the TJ-II experience - López-Bruna, D.; Romero, J.; Vargas-Blanco, Iván (Institute of Physics Publishing, 2015)
The TJ-II stellarator is a mid-size Heliac design (high rotational transform, low magnetic shear) that allows for external control of the rotational transform profile. The long experience with locating diverse magnetic resonances at different plasma radii has assessed their reliability as transport controllers: in low density electron cyclotron heating plasmas, a "transport barrier effect" is found in most of the confinement zone accompanying magnetic resonances; in higher density and beta plasmas under neutral-beam heating operation, resonant layers show a clear incidence on the access to the H-mode of confinement or, likewise, on the back transition to L-mode. Moreover, confinement events similar to tokamak phenomenology have been also related with magneto-hydrodynamic activity around the magnetic resonances and are, consequently, amenable to external control. All in all, the TJ-II experience posits magnetic resonances as natural transport and stability controllers in toroidal plasmas. Further studies must either confirm or set operational limits to these findings.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938152603&partnerID=40&md5=e6f3d0763d15678fc171d2574afc1cad
Keywords: Controladores; Resonancia magnética; Magnetismo; Plasma; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion